1984
DOI: 10.1051/rnd:19840105
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychosomatic stress at the end of pregnancy on maternal and fetal plasma cortisol levels and liver glycogen in guinea-pigs

Abstract: Summary. Plasma cortisol and liver glycogen were measured in the mother, fetus and newborn of guinea-pig after a stress on days 60 and 67 of gestation (parturition occurring on day 68) ; at those times, the animals were held for 3 h in the dark and subjected to a flash of 75 J intensity every 10 sec. In comparison with the controls, stress increased plasma cortisol in both mothers and fetuses. While it decreased maternal liver glycogen on day 60, it increased fetal liver glycogen at the same stage. Glycemia de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…In rats, maternal and fetal plasma corticosterone are significantly elevated after maternal stress [79,105]. In the guinea pig, cortisol concentrations in the maternal plasma are 10-fold those in the fetus, and as for the rat, maternal stress results in significant increases in plasma glucocorticoid concentrations in both mother and fetus [81,106]. An important study has shown that greater glucocorticoid transfer occurs across the placenta of female compared to male fetuses [107].…”
Section: Glucocorticoids: the Endocrine Programming Factormentioning
confidence: 98%
“…In rats, maternal and fetal plasma corticosterone are significantly elevated after maternal stress [79,105]. In the guinea pig, cortisol concentrations in the maternal plasma are 10-fold those in the fetus, and as for the rat, maternal stress results in significant increases in plasma glucocorticoid concentrations in both mother and fetus [81,106]. An important study has shown that greater glucocorticoid transfer occurs across the placenta of female compared to male fetuses [107].…”
Section: Glucocorticoids: the Endocrine Programming Factormentioning
confidence: 98%
“…Animal studies suggest that glucocorticoids can be important ‘fetal programming’ factors in prenatal stress protocols. In rodent models prenatal stress has been shown to result in up‐regulation of glucocorticoid concentrations in both mother and fetus (Dauprat et al 1984; Cadet et al 1986) and excessive exposure of the fetus to maternal steroids may constitute at least part of the programming stimulus. (Dodic et al 1999; Seckl, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, maternal and fetal plasma corticosterone are significantly elevated after maternal stress (Takahashi et al, 1998;Koehl et al, 1999). In the guinea pig, cortisol concentrations in the maternal plasma are 10-fold those in the fetus, and as for the rat, maternal stress results in up-regulation of endogenous glucocorticoid concentrations in both mother and fetus (Dauprat et al, 1984;Cadet et al, 1986). Interestingly, it has been shown that greater endogenous glucocorticoid transfer occurs across the placenta of female compared to male fetuses (Montano and Wang, 1993).…”
Section: The 'Glucocorticoid Hypothesis'mentioning
confidence: 94%